HUBUNGAN PENGETAHUAN SIKAP DAN TINDAKAN REMAJA PUTRI TERHADAP KEBERSIHAN ORGAN GENITALIA SAAT MENSTRUASI DI SMPN 20 PEKANBARU TAHUN 2022 - Nadia Rahmanisa; Nurhapipa Nurhapipa; Alhidayati Alhidayati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Keeping the external genitalia clean is the first step in maintaining reproductive health. The female reproductive organs are indeed much more complicated and susceptible to disease because anatomically, the female reproductive organs are located inside the body, where the female reproductive organs are located in the body. and urethra making it easier for germs to enter. The purpose of this study was to determine whether there was a relationship between knowledge, attitudes and actions on the cleanliness of the genital organs during menstruation. The type of research used in this study is quantitative with a cross sectional research design, the sampling technique used is non-probability sampling using a proportional sampling technique, the location of this research is at SMPN 20 Pekanbaru with a population of 392 female teenagers with a research sample of 82 people. It was found that there was a relationship between action and cleanliness of adolescent genital organs with P Value 0.036 <0.05. And POR 1.208 (0.496 – 2.946). And the absence of a relationship between knowledge and attitudes towards the cleanliness of adolescent genital organs obtained P Value 0.445 > 0.05 and POR POR = 1.520 (0.610-3.786), P Value 0.521 > 0.05. And POR POR = 0.046(0.261-1.596). It is hoped that the school can provide health education to their students and the health center to be able to foster youth to understand the importance of maintaining the cleanliness of the reproductiv